Navigating water discord: a review of water conflicts in the common resource management system in coastal areas - Hasan, Md Hasibul; Hossain, Mohammad Jobayer; Nipa, Sultana Afrin (Frontiers in Water, 2025)
Water disputes are a prevalent global concern because of the scarcity of freshwater supplies and intricate interplay between hydrology, environment, and society. Water disputes can arise due to a variety of factors, including interests of stakeholders, allocation of resources, process of decision-making, power dynamics, and governance system. If left unresolved, these confrontations have the potential to escalate into acts of violence. This review focuses on the evolution and dynamics of local-level water conflicts that received limited attention but has significant impact on Community-Based Natural Resource Management, with a deep-dive focus on coastal Bangladesh. We examined the history of water management and causes and impacts of water conflicts in coastal polders from macro to micro scale along with identifying the strategies and approaches to eliminate water conflicts at local-level. The findings emphasize the need for stakeholder engagement, collaborative approaches, and improved water management strategies to mitigate conflicts and promote sustainable water resource management. The findings emphasize on the redistribution and decentralization of power and interest-based resource management system, collaborative approach and stakeholder engagement, a mix method approach presence of Irrigation Management Transfer, participatory irrigation management, transformative analysis, and improved water management strategies to mitigate conflicts and promote sustainable water resource management.